Variasi Bahasa dalam Media Sosial Twitter - Rizkiyah Afdhaliyah; Siti Chairunnisa Haq (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Language is a communication tool that is usually used by people to work together and interact. Language variation is closely related to language and society. This research on language variations that occur on Twitter social media aims to find out how the meaning of language variations in Twitter social media. There are two languages ​​studied, namely (1) slang whose data is taken from the @Ivanasha, @usaiusulhh, and @aldapstsr accounts, and (2) Javanese whose data is taken from the @nksthi account. This research uses a qualitative approach, with descriptive analysis method. This study collects non-interactively data. The source of the data is humans who work as subjects or key informants. The research is sociolinguistic studies. This study was chosen because this study looks at the use of language that includes language variation.